2013
DOI: 10.1021/ef3018578
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Petroleum Composition. 3. Asphaltene Aggregation

Abstract: Molecular characterization of asphaltenes by conventional analytical techniques is a challenge because of their compositional complexity, high heteroatom content, and asphaltene aggregate formation at low concentrations. Thus, most common characterization techniques rely on bulk properties or solution-phase behavior (solubility). Proposed over 20 years ago, the Boduszynski model proposes a continuous progression in petroleum composition (molecular weight, structure, and heteroatom content) as a function of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
202
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(217 citation statements)
references
References 116 publications
14
202
1
Order By: Relevance
“…Mass fraction of asphaltenes is computed by Eq. (11). The calculated asphaltene mass percentage with depth and time is shown in Figure 14.…”
Section: Resultsmentioning
confidence: 99%
“…Mass fraction of asphaltenes is computed by Eq. (11). The calculated asphaltene mass percentage with depth and time is shown in Figure 14.…”
Section: Resultsmentioning
confidence: 99%
“…15,22 Recent time-of-flight data are consistent with this range of molecular weights. 24 On the other hand, Eyssautier et al 25 observed a range of aggregates an order of magnitude larger than the VPO data based on a combination of ultracentrifugation and X-ray scattering measurements. This difference can only partially be attributed to the difference between molar averages (VPO) and mass averages (scattering) but could be explained by flocculation of the aggregates, which would not be detected by VPO measurements.…”
Section: ■ Introductionmentioning
confidence: 88%
“…1,[16][17][18][19][20][21][22][23][24][25][26][27] The disparity of these measurements has been suggested to result from the tendency of asphaltenes to aggregate. 27,28 In the past decades, two structural models have been debated for asphaltene molecules: the island model and the archipelago model. 16,[19][20][21][22]29 The island model (sometimes referred to as the continental model 30 ) has only one aromatic core with peripheral alkyl chains, whereas the archipelago model has multiple aromatic cores that are bridged by alkyl chains and may also contain peripheral alkyl chains.…”
Section: Introductionmentioning
confidence: 99%